Effects of Fiber Orientation Variation on Tensile Strength of Bamboo Fiber Reinforced Composite Using Polyester Resin Type Bqtn-157-EX - Ahmad Nayan; Teuku Hafli (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This article presents the results of investigations on composite materials reinforced with natural fibers from bamboo trees with variations in fiber direction. Because of the promising potential of the bamboo plant where its availability is abundant and sustainable, research on the mechanical properties of bamboo fiber is still very interesting to do to gain the maximum of it potential. Bamboo fiber is extracted from bamboo stems by beating. Treatment with soaking in 5% alkaline for 120 minutes was carried out before the specimen was made using an epoxy resin matrix. The process of making composite materials is carried out using the resin infusion method. Composition Specimens were prepared with a volume fraction of 40% and 60% for resin and fiber, respectively. And variations in fiber direction are set at 30, 45, and 60 degrees. The characteristics of the mechanical properties were obtained by testing the dance using a universal testing machine, while the bond characteristics between the matrix and the fibers were observed through micro-observation using the SEM tool. The specimen in a fiber orientation of 30° performs the strongest tensile strength of 165.9 MPa.